GAMBARAN Candida albicanss PADA URIN REMAJA DI PANTI ASUHAN X BANJARMASIN - Yunita Hafizah; Yuliana Salman; Risnawati Risnawati; Hajrah Hidriya (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2022)
Candida albicans is one of the most pathogenic species and often causes vaginitis in women with the main symptom of vaginal discharge. As many as 75% of women in Indonesia have experienced vaginal discharge at least once in their life and half of them have experienced vaginal discharge twice or more. This study aims to calculate the percentage of Candida albicanss in the urine of adolescents at the Putri Orphanage in Banjarmasin. This type of research is quantitative and descriptive with a cross-sectional design. The research sample was 21 urine sample teenagers at the Orphanage in Banjarmasin. The sampling technique used was purposive sampling. Laboratory examinations included macroscopic observations of Candida colonies growing on Sabouraud Dextrose Agar (SDA) media, and microscopic observations using the Germ Tube test to distinguish Candida albicanss species from Candida non-albicanss. And by filling out a questionnaire to determine the level of knowledge about vaginal discharge and personal hygiene. The results showed 33% of respondents were positive for Candida albicanss. Based on the results, overview Candida albicans in adolescents at the Putri Asri Orphanage in Banjarmasin, it can be concluded that there are 7 samples (33%) positive for Candida albicans. Personal hygiene and environmental sanitation can affect the growth of Candida albicans which can cause vaginal discharge in adolescent girls.